FAKTOR FAKTOR YANG MEMPENGARUHI MOTIVASI MAHASISWA INGIN MENJADI WIRAUSAHA - Indah Ariffianti; Nizar Hamdi (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
The objectives of this research are a). to determine the effect of various factors, including socio-demographic (socio demographic), the attitude of the individual (personal attitude) and contextual (contextual), either partially (individually) or simultaneously (together) against the motivation of student entrepreneurship at STIE AMM Mataram , b). to know of socio-demographic factors (socio demographic), the attitude of the individual (personal attitude) and contextual (contextual) the dominant influence on the student entrepreneurial motivation STIE AMM Mataram. This study was designed with descriptive research aimed to describe some of the factors that influence the motivation of students want to become entrepreneurs and to use the analysis of multiple regression, T test and F test will be known which of the factors of sociodemographic (socio demographic), the attitude of the individual (personal attitude) and contextual (contextual), which have a significant effect either partially or simultaneously, and the dominant influence on the motivation of the students want to become entrepreneurs. The survey results revealed that together socio demographic (socio demographic), the attitude of the individual (personal attitude) and contextual (contextual), significantly affect the motivation Entrepreneurial Students STIE AMM Mataram as evidenced by the results of the F count> F table (8517 > 3:34), then H0 is rejected and Ha accepted, meaning that there is significant influence between independent variable (Social Factors Demographics, Attitudes and Factors Contextual Factors) together on the dependent variable (Student Entrepreneurial Motivation) at STIE AMM Mataram. Based on the results of partial test (t test) can be explained that a significant difference between Social Factors Demographics (X1) to Motivation Entrepreneurial Students at STIE AMM Mataram, this is evidenced by the value t count> t table (4,051> 2,048), the Ha accepted and H0 rejected, meaning that partially positive and significant impact terhadapa Student Entrepreneurial Motivation STIE AMM Mataram, which is reinforced by the significant level of 0.000 <0.05. But for the attitude factor (X2). Based tcount <ttable (0.810 <2.048), the Ha rejected and H0 is accepted, meaning that partially no significant difference between the attitude of factors (X2) to the Student Entrepreneurial Motivation at STIE AMM Mataram. It is on show as well with significance level is 0423> 0.05. Similarly to the Contextual Factors (X3) based tcount<ttable (0581 <2048) then Ha is rejected and H0 is accepted, meaning that partially no significant difference between the Contextual Factors (X3) against Motivation Entrepreneurial Students at STIE AMM Mataram. It is on show as well with significance level is 0565>0.05